Pengaruh Air Laut terhadap Kapasitas Beban pada Balok Beton Bertulang yang Diperkuat GFRP-S dengan Perendaman selama Satu Tahun - Asri Mulya Setiawan; Erniati Bachtiar (Indonesian Journal of Fundamental Sciences, 2018)
The test results on specimens without GFRP-S reinforcement showed that there was a decrease in load capacity for BN0 specimens of 1.383%. Decrease in BN6 test material capacity after soaking sea water for 6 months. Whereas for specimens with reinforcement of GFRP-S shows a decrease in maximum load on BF6 and BF12 specimens against BF0 test objects. The percentage of decrease in loads is 3.898% and 4.285%, respectively. Decreased load capacity of BF12 specimens after 12 months of seawater immersion. This is due to a decrease in the capacity of the bond on the GFRP along with the soaking time, thus accelerating the occurrence of debonding.